Direct ink writing of zirconia three-dimensional structures. Issue 24 (24th May 2017) - Liao, Jingjing; Chen, Hehao; Luo, Hang; Wang, Xiaofeng; Zhou, Kechao; Zhang, Dou
Abstract : Fabrication of 3D structures by DIW using ZrO2 ink with optimized NH4 PAA concentration. Abstract : Tailoring the rheological properties of colloidal inks is critical for the direct ink writing of three-dimensional structures. The rheological properties of zirconia colloidal inks are extremely sensitive to the concentration of ammonium polyacrylate (NH4 PAA). The colloidal ink containing 47 vol% ZrO2, 0.005 g ml −1 cellulose and 0.8 wt% NH4 PAA dispersant showed a low viscosity of 3 Pa s at a characteristic shear rate of 50 s −1 and maintained an equilibrium elastic modulus of 8 × 10 4 Pa when the stress amplitude was up to 200 Pa. Three-dimensional structures with a feature size of 200 μm were successfully assembled with fine integrity.